Условия построения бездатчиковых электромеханических систем на основе бесконтактных двигателей с постоянными магнитами - Акинин, К.П. (Технічна електродинаміка, 2011)
Development features of sensorless electromechanical systems on the basis of permanent magnet brushless motors are considered. Example of pulse-width modulation algorithm for sensorless control are given. References